CYBER PUBLIC RELATIONS MODEL IN BUILDING A POSITIVE IMAGE OF LOCAL GOVERNMENT: (Case Study on the Government of Special Capital Region of Jakarta) - Ningsih, Hikmah; Umarella, Farid (Advances in Social Sciences Research Journal, 2020)
The utilization of online media, known as Cyber Public Relations (CPR), is the online public relations activities for information dissemination using online media by government institutions as an agenda to build the image of the institution in the public eyes. The purpose of this study was to determine and analyze the model of Cyber ​​Public Relations and the obstacles in utilizing the online media of the DKI Jakarta Provincial Government in building a positive image of the institution. The paradigm used in this research is the constructivist paradigm. This research is using a qualitative research approach with a case study research method. Data collection techniques include: (1) in-depth interviews (2) observations, and (3) study of relevant literature. The process of analyzing qualitative data is carried out in stages: data reduction, then presenting the data and finally verifying (drawing conclusions). The results showed that through two official websites, namely the official website www.jakarta.go.id as a data information center and www.beritajakarta.com as the official portal for reporting. In addition, it has a number of social media, twitter, facebook, Instagram and YouTube as a means of information to the public. It is also supported by JAKI as an application that is the gateway for the community to access all online services for the DKI Jakarta Provincial Government. Cyber ​​PR is used in synergizing communication between DKI Jakarta regional government and the community so that it can produce a better image of government in the community.